MOLECULAR CHARACTERIZATION OF POTATO SOMATIC HYBRIDS BY INTER SIMPLE SEQUENCE REPEAT (ISSR) MARKERS - Tiwari, Jagesh K; Poonam, Poonam; Saurabh, Shaumaya; Devi, Sapna; Ali, Nilofer; Bhardwaj, Vinay; Singh, B P (Potato Journal, 2015)
In this study, potato somatic hybrids of Solanum tuberosum ‘C-13’ (+) S. pinnatisectum; and C-13 (+) S. etuberosum were analyzed using 16 inter simple sequence repeat (ISSR) markers. In somatic hybrids C-13 (+) S. pinnatisectum, out of total 149 bands, 100 bands were polymorphic and 49 monomorphic, whereas in somatic hybrids C-13 (+) S. etuberosum from total 168 bands 130 were polymorphic and 38 monomorphic. Cluster analysis based on the Jaccard’s similarity coefficient showed genetic distinctness among clones of both the hybrids, for example C-13 (+) S. pinnatisectum (13 groups) and C-13 (+) S. etuberosum (25 groups) except P3 and P4, P7 and P8, and E8 and E10 showed maximum similarity coefficient (0.96- 0.97). All somatic hybrids analyzed by cluster analysis were clearly separated on the principal component analysis plot. As a result, here we show that ISSR markers confirmed hybridity of somatic hybrids by possessing parent-specific bands and molecular diversity among the clones for their use in potato breeding.